2012
DOI: 10.1007/s00405-012-2083-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of photodynamic therapy with temoporfin in curative treatment of recurrent carcinoma of the oral cavity and oropharynx

Abstract: Therapeutic options for recurrent carcinoma of the upper aérodigestive tract (UADT) are limited. The prognosis of these tumours remains poor with significant rate of recurrence and a lower median survival time. Photodynamic therapy (PDT) is a relatively new therapeutic alternative which combines the use of a photosensitising agent and light to induce a cytotoxic effect on the tissues. This is a retrospective single-centre study carried out in patients with a recurrence of an oral cavity or oropharyngeal carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…m-THPC-PDT has been used in curative treatment for patients with the head and neck cancer [ 15 ]. Emerging reports have shown that m-THPC-PDT could be a promising application for the treatment of other malignant neoplasm, such as the liver, oral cavity, and oropharynx cancer [ 16 , 17 ]. The cell lines SW480 and SW620, derived from a surgical specimen of a primary colon adenocarcinoma and a lymph node metastasis of the same patient respectively, are a useful patient-matched model for studying colorectal cancer treatment in vitro [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…m-THPC-PDT has been used in curative treatment for patients with the head and neck cancer [ 15 ]. Emerging reports have shown that m-THPC-PDT could be a promising application for the treatment of other malignant neoplasm, such as the liver, oral cavity, and oropharynx cancer [ 16 , 17 ]. The cell lines SW480 and SW620, derived from a surgical specimen of a primary colon adenocarcinoma and a lymph node metastasis of the same patient respectively, are a useful patient-matched model for studying colorectal cancer treatment in vitro [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 5‐ALA is highly hydrophilic and has low penetration into the plasma membrane, necessitating high doses and prolonged incubation time to achieve an ideal therapeutic intracellular PpIX concentration . Several illumination tools and a new generation of photosensitizers have been developed to overcome these obstacles; however, recurrences of some head and neck tumors (including OSCC) after PDT have been reported , suggesting some resistance to the treatment, likely deriving from these technical difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Durbec et al in 2013 examined the efficacy and safety of PDT in recurrent carcinoma of the oral cavity and oropharynx using Foscan, and observed a 93% complete response rate. 8 Jerjes observed a 5 year survival of 84.2% and a recurrence rate of 15.8% in T1–2 SCCA of the oral cavity treated with up to three rounds of mTHPC. 9 Biel, in a series of 113 oral cavity PDT patients, with 93.8% of patients with Cis-T2 tumors and 89.6% of patients with superficial T2–3 tumors remaining free of disease after a mean follow up of 90 months.…”
Section: Pdt For Early Stage Sccmentioning
confidence: 97%